CHINA AND RUSSIA : FOUR CENTURIES OF CONFLICT AND CONCORD - Snow, Philip, 1952- (New Haven : Yale University Press, 2023)
c
t Rebellion-- t
Includes index
Bibliography page: [573]-584
Keywords: Russia -- Foreign relations -- China; Soviet Union -- Foreign relations -- China; Russia (Federation) -- Foreign relations -- China; China -- Foreign relations -- Russia; China -- Foreign relations -- Soviet Union; China -- Foreign relations -- Russia (Federation)